Pemanfaatan Tanaman Kelor (Moringa oleifera) sebagai Obat Tradisional di Dusun Aek Kulim Mandalasena Kabupaten Labuhanbatu Selatan - Sri Rahayu; Rosmidah Hasibuan (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Moringa leaves are one part of the plant that has been widely researched for its nutritional content and usefulness. Moringa is an important plant from the moringaceae family that has many uses. Every part of this tree has benefits as a source of medicine, food, beauty products, industrial purposes. Traditional medicinal plants are types of plants that have medicinal functions and are used to cure or prevent various diseases. The purpose of this study is to determine the utilization of Moringa plants in Aek Kulim Mandalasena Hamlet, Silangkitang District, South Labuhanbatu Regency. By using data collection techniques in the form of observation and interviews with informants and people who utilize moringa plants used as traditional medicine. Moringa leaves are used as traditional medicine to cure or prevent various diseases such as lowering high blood pressure, helping to relieve aches due to gout and rheumatism, strengthening the uterus and the most important thing is to cure / prevent cancer. In addition to traditional medicine, moringa leaves are also used for daily preparations such as fresh vegetables, clear vegetables, and stir-fried vegetables.